Perceptions of risk in the mining industry. (19th June 2007) - Dunbar, W. Scott
Framing, ambiguity aversion, and the affect heuristic greatly influence decision-making under uncertainty. Framing is the expression of equivalent options in terms of gains or losses. The risk of options might be due to their associated ambiguity. The affect heuristic is an emotional response to stimuli such as words which leads to a perception of the risk of options. The role these concepts play in decision-making situations in mining is discussed. The affect heuristic seems to be significant to risk perception in mining but it is poorly understood, which has implications for risk management and communication in the mining industry.